PERENCANAAN PEMBELAJARAN PAI BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) DI ERA SOCIETY 5.0: STRATEGI DAN IMPLEMENTASI - Juni Erpida Nasution (STAI Nurul Falah Airmolek, 2024)
The Society 5.0 era, which is characterized by the integration of smart technology in everyday life, demands significant changes in educational practices, including Islamic Religious Education (PAI). To answer this challenge, PAI needs to integrate Higher Order Thinking Skills (HOTS) into its curriculum, with the aim of producing students who not only understand religious teachings but also have critical, creative and solution thinking skills. Strategies such as a contextual learning approach that links Islamic teachings with social issues and the use of digital technology can be used to strengthen the learning process.Research shows that implementing HOTS has a positive impact on students' critical thinking and problem solving abilities. However, challenges remain, including limited teacher knowledge about the HOTS method and inadequate technological facilities. Therefore, continuous teacher training and support from technological facilities are needed to ensure that technology-based learning can run effectively